2009
DOI: 10.1242/jcs.049767
|View full text |Cite
|
Sign up to set email alerts
|

AIMP2 promotes TNFα-dependent apoptosis via ubiquitin-mediated degradation of TRAF2

Abstract: AIMP2 (aminoacyl-tRNA synthetase interacting multifunctional protein 2; also known as JTV-1) was first identified as p38 in a macromolecular protein complex that consisted of nine different aminoacyl-tRNA synthetases and two other auxiliary factors. AIMP2 also plays pivotal roles in the regulation of cell proliferation and death. Although AIMP2 was previously shown to augment TNFα-induced cell death, its working mechanism in this signal pathway was not understood. Here, we investigate the functional significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 30 publications
2
61
0
Order By: Relevance
“…S3I and S3J). Blockade of Wnt ligand secretion by a porcupine inhibitor, IWP4 (32), revealed that the increased Wnt/b-catenin signaling in Aimp2 Previous studies suggested that AIMP2 is involved in ubiquitination-dependent degradation of TRAF2 and p53 (17,18) by the direct interaction. Thus, we tested whether AIMP2 modulates the Wnt/b-catenin signaling by ubiquitination of DVL1.…”
Section: Aimp2 Inhibits Wnt/b-catenin Signalingmentioning
confidence: 99%
See 4 more Smart Citations
“…S3I and S3J). Blockade of Wnt ligand secretion by a porcupine inhibitor, IWP4 (32), revealed that the increased Wnt/b-catenin signaling in Aimp2 Previous studies suggested that AIMP2 is involved in ubiquitination-dependent degradation of TRAF2 and p53 (17,18) by the direct interaction. Thus, we tested whether AIMP2 modulates the Wnt/b-catenin signaling by ubiquitination of DVL1.…”
Section: Aimp2 Inhibits Wnt/b-catenin Signalingmentioning
confidence: 99%
“…Coimmunoprecipitation was performed as described previously (17). The cells were lysed in protein lysis buffer (0.1% NP-40, 25 mmol/L Tris, 0.5 mmol/L EGTA, 10 mmol/L NaCl, 0.5 mmol/L MgCl 2 , 1 mmol/L EDTA, proteinase/phosphatase inhibitor cocktail).…”
Section: Coimmunoprecipitationmentioning
confidence: 99%
See 3 more Smart Citations